Complete chloroplast genome sequence of Passiflora serrulata Jacq. (Passifloraceae). Issue 1 (2nd January 2021) - Mou, Hai-Fei; Huang, Wei-Hua; Liu, Jie-Yun; Wen, Fang; Tian, Qing-Lan; Wu, Yan-Yan; Fu, Long-Fei; Zhang, Ying-Jun; Wei, Yi-Gang
Abstract: This study was the first report for the complete chloroplast genome of Passiflora serrulata Jacq. (Passifloraceae). The cp genome was 149, 683 bp in length contained two inverted repeats (IRs) of 25, 470 bp, which were separated by large single-copy (LSC) and small single-copy (SSC) of 86, 252 bp and 13, 491 bp, respectively. A total of 110 functional genes were encoded, comprised 76 protein-coding genes, 30 tRNA genes, and four rRNA genes. The GC content was 37.0%. The maximum likelihood phylogenetic tree indicated that P. serrulata was recovered as the member of subg. Passiflora and most closely related to the clade formed by P. serratodigitata and P. ligularis .